1994
DOI: 10.1152/ajpendo.1994.266.2.e242
|View full text |Cite
|
Sign up to set email alerts
|

Acute noradrenergic activation induces insulin resistance in human skeletal muscle

Abstract: We assessed in normal subjects the effects of an acute increase in forearm norepinephrine (NE) release, evoked by -20 mmHg lower body negative pressure (LBNP), on insulin-mediated muscle glucose uptake. Seven normal subjects underwent the following two insulin euglycemic clamps in random sequence: one during application of LBNP and the other without LBNP (control study). In the control study, hyperinsulinemia (approximately 60 microU/ml) produced a significant increment in forearm NE release, measured by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 30 publications
1
71
1
2
Order By: Relevance
“…Resting heart rate is a marker of the autonomic nervous system, with elevated heart rate reflecting a shift in autonomic balance toward enhanced sympathetic nervous activity and reduced vagal tone (21). Some evidence suggests that sympathetic activation contributes to the development of insulin resistance in humans (7,8,22,23). A pilot study showed that 3 months after renal denervation, fasting glucose concentrations were reduced in patients with resistant hypertension, suggesting that the sympathetic nervous system may directly modulate the glucose metabolism (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resting heart rate is a marker of the autonomic nervous system, with elevated heart rate reflecting a shift in autonomic balance toward enhanced sympathetic nervous activity and reduced vagal tone (21). Some evidence suggests that sympathetic activation contributes to the development of insulin resistance in humans (7,8,22,23). A pilot study showed that 3 months after renal denervation, fasting glucose concentrations were reduced in patients with resistant hypertension, suggesting that the sympathetic nervous system may directly modulate the glucose metabolism (24).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated heart rate has been associated with an increased risk of type 2 diabetes in a number of epidemiological studies (1,2,3,4,5). This association has been mainly attributed to increased insulin resistance, secondary to the activation of sympathetic nerve activity (6,7,8). However, only one small longitudinal study (7) has assessed the predictive value of sympathetic activity on the development of insulin resistance and fasting hyperglycaemia, using surrogate measures of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…insulin-mediated glucose uptake in skeletal muscle. 24 In non-dippers, the sympathetic tone is believed to be increased at night, suggesting that they have nocturnal autonomic dysfunction. 25 Obese patients have increased prevalence of non-dipping status, 26 and in this study, non-dippers had a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the cause of sympathetic hyperactivity in HT is insulin resistance because this frequent concomitant of a high-BP state leads to hyperinsulinemia, which is known to either increase sympathetic nerve traffic or to stimulate NE secretion from the sympathetic nerve endings, all effects being greater in subjects with HT. 27,28 It should be emphasized, however, that sympathetic activation has in turn been shown to cause insulin resistance, 29,30 so that it is still uncertain which of the 2 alterations precedes and determines the other. In a recent longitudinal study by Japanese investigators, an increase in plasma NE was seen years before the increase in plasma insulin levels also became manifest, 31 suggesting the derangement in glucose metabolism to follow rather than precede the sympathetic derangement.…”
Section: Mancia Et Al Sympathetic Overactivity In Hypertensionmentioning
confidence: 99%